Anticoagulants and the Björk-Shiley prosthesis. Experience of 390 patients. - Sutton, M G (1978)
From September 1972 to January 1975, 390 patients underwent valve replacement using the Björk-Shiley tilting disc prosthesis. For the group as a whole hospital mortality was 13.3 per cent and was lowest in those undergoing isolated mitral or aortic valve replacement (5.3 and 9.4%, respectively). Available for follow-up were 209 patients of whom 123 were maintained on dipyridamole and 96 on warfarin. Thromboembolic complications were significantly (P less than 0.01) commoner in the dipyridamole (28 of 123, 22%) than warfarin (6 of 86, 7%) treated group. In the dipyridamole treated group the incidence of thromboembolic complications was similar whichever valve was replaced and thromboembolic complications were responsible for 14 of the 28 late deaths. In the warfarin treated group thromboembolic complications only occurred in patients with a mitral prosthesis. Anticoagulation is indicated for all patients with this prosthesis wherever inserted.